2003
DOI: 10.1897/1551-5028(2003)022<0845:trsofb>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Sensitivity of Four Benthic Invertebrates to Metals in Spiked-Sediment Exposures and Application to Contaminated Field Sediment

Abstract: The relative sensitivity of four benthic invertebrates (Hyalella azteca, Chironomus riparius, Hexagenia spp., and Tubifex tubifex) was determined for Cd, Cu, and Ni in water-only and in spiked-sediment exposures. Survival (median lethal concentrations [LC50s] and the concentrations estimated to be lethal to 25% of test organisms [LC25s]), and endpoints for growth and reproduction (mean inhibitory concentrations [IC25s]) were compared. The sensitivities differed depending on the species and metal, although some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
42
1
9

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 31 publications
12
42
1
9
Order By: Relevance
“…The latter include reduction in growth (Milani et al 2003), reproduction (Gillis et al 2002) and hormonal activity (Chen et al 1994) and an increase in mucus production (Bouché et al 2000) and autotomy (Brković-Popović & Popović 1977, Lucan-Bouché et al 1999, Bouché et al 2000. Autotomy followed by regeneration of a broken caudal body part is commonly observed in oligochaetes suffering from various stressors such as predation and toxicant exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The latter include reduction in growth (Milani et al 2003), reproduction (Gillis et al 2002) and hormonal activity (Chen et al 1994) and an increase in mucus production (Bouché et al 2000) and autotomy (Brković-Popović & Popović 1977, Lucan-Bouché et al 1999, Bouché et al 2000. Autotomy followed by regeneration of a broken caudal body part is commonly observed in oligochaetes suffering from various stressors such as predation and toxicant exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that different species may show different responses to the same level of sediment contamination (Ingersoll et al, 2002;Milani et al, 2003). For this reason, the amphipods C. multisetosum and M. gryllotalpa were selected, since both are regarded as "keystone species" in their respective ecosystems and thus toxicity tests should reflect ecosystem impact .…”
Section: Discussionmentioning
confidence: 99%
“…Oligochates have attracted attention as possible organisms for sediment quality evaluation in general environmental quality assessments (e.g. Ankley et al 1991 andTuikka et al 2011) as well as in specific toxicity tests for metals (Milani et al 2003 andHirsch, 2009) and organic chemicals (West et al 1997 andDing et al 2001) including pesticides (Keilty et al 1988). Of the seven families of aquatic microdrile oligochaetes three, the Naididae, Tubificidae and Lumbriculidae, have received most attention for selection as toxicity test organisms.…”
Section: Ecology Of Relevant Speciesmentioning
confidence: 99%
“…West et al 1997, Milani et al 2003Keilty et al 1988, Smith et al 1991 or in the evaluation of the quality of environmental sediments. Of the three main oligochaete families tubificids are easily cultured in the laboratory (Reynoldson et al 1991Ducrot et al 2007) and have recognizable life history stages, that are, cocoons, newly hatched worms, immature worms, and mature worms.…”
Section: Test Endpointsmentioning
confidence: 99%
See 1 more Smart Citation